Pengaruh Faktor Psikologis terhadap Keputusan Menabung Mahasiswa pada Bank Syariah di Universitas Negeri Padang - Mandali, Ronaldo; Rahmiati, Rahmiati; Mesta, Hendri Andi (Jurnal Kajian Manajemen Bisnis, 2016)
The purpose of this research is to analyze the influence of psychological factors on Saving Decision on Bank Syariah in Padang State University. The variables used in this research are motivation, perception, learning, and Consumer Attitudes. The population in this study are Padang State University students who have never used the savings in one of the Islamic Bank in the city of Padang. The sampling technique used purposive sampling with 100 respondents. Analysis tool used is multiple linear regression analysis, using SPSS version 23. The results of this study indicate that: (1) motivation, perception, learning, and attitude significantly influence the Saving Decision on Bank Syariah in Padang State University. (2) Perception is the most dominant factor in influencing Saving Decision.